PERAN GURU PAI DALAM PEMBENTUKAN KARAKTER SISWA DI ERA REVOLUSI INDUSTRI 4.0 - salamah salamah (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2020)
Globalization has had such a huge impact on the nation's generation, one ofwhich is the degradation of characters who are increasingly unstoppable among students.The role of Islamic Religious Education teachers is increasingly complex in the IndustrialRevolution era 4.0. The teacher is not only required to master the learning material, butthe teacher is required to instill character. From this background gives encouragement tothe author to conduct research on how the Role of Islamic Religious Education Teachersin the Formation of Student Character in the Era of the Industrial Revolution 4.0Revolution. This type of research is a descriptive qualitative field research. The datacollection method is by interview, observation, or field notes, and communication.Whereas data analysis uses descriptive analytic and finally conclusions. The purpose ofthis study was to ditermine the role of islamic religious education teachers in shapingstudent characte. The results showed that in forming the character of students of SMAN 9Kerinci used a comprehensive approach. As for the character values possessed namelyreligious, responsibility, honesty, creative, democratic, disciplined, independent, tolerance,hard work, caring for the environment, polite, and simple.